Hypolipidemic Effects of Eryngium Caucasicum Leaves Extract on Rats with Induced Diabetes Mellitus - Glaucio Dire Feliciano (مجلة الانبار للعلوم البيطرية, 2024)
This research aimed to assess the hypolipidemic effects of an extract from Eryngium caucasicum in a Rat model of Type 2 Diabetes Mellitus produced by Streptozotocin. Forty adult male Wistar rats were divided into five groups, with a total of eight rats in each: (1) healthy control rats, (2) diabetic rats with no diabetes, (3) diabetic rats given insulin, (4) diabetic rats given 200 mg/kg orally for 30 days of Eryngium caucasicum extract, and (5) diabetic rats given 300 mg/kg orally for 30 days. Injecting Nicotinamide and Streptozotocin intraperitoneally caused diabetes. Fasting blood sugar, hepatic enzymes, and lipid profiles were determined from blood samples taken after the trial. The levels of HDL were increased significantly in G3, G4, and G5 compared to G2. The insulin group and the group given 300 mg/kg of Eryngium caucasicum substantially reduced LDL cholesterol compared to the G2. It should be mentioned that the diabetic control group had higher TC compared to the healthy control group after rat diabetes induction (P = 0.020). Compared to the G2, G3 treated with insulin and groups treated with extract at dosages of 200 as well as 300 mg/kg body weight had a substantially lower TC (P < 0.01). Serum TG was improved when insulin and Eryngium caucasicum extract were administered at 200 and 300 mg/kg dosages, respectively (P < 0.05). Serum ALT and AST levels were shown to be elevated after STZ diabetes induction as compared to the G1. Even though diabetic rats' ALT and AST levels were enhanced by insulin and all 2 plant trial dosages, 200 and 300 mg/kg. In summary, our findings suggest that the antidiabetic, hypolipidemic, and hepato-protective properties of Eryngium caucasicum, when administered to an animal model of Type 2 diabetes mellitus, may vary with dosage. [AJVS 2024; 17(2.000): 1-7]